(untitled) (Jurnal Agribisnis dan Agrowisata, 2026)
Tuna Marketing in Fish Auction Muncar District, Banyuwangi Regency. The trade system for tuna is faced with the long channel of the trade system that has been formed so far. This research aims to determine the marketing channels, marketing functions, marketing efficiency, as well as the structure and behavior in the marketing of tuna in TPI Muncar District. There are 16 fishermen and eight traders as respondents. The data collected are primary data and secondary data using the methods of observation, interview, and documentation. The result of research show that there were three marketing channels for tuna, namely fishermen – collectors – wholesalers – retailers – consumers (channel I) totaling nine fishermen, fishermen – wholesalers – home industry (channel II) totaling seven fishermen, and fishermen – retailers – concumers (channel III) totaling 16 fishermen. Trading functions include the exchange functions, physical functions, and facility functions. Based on the analysis, channel II is the most efficient channel with the smallest trading margin (IDR 3,000.00/kg), the largest farmer’s share (85%), and the largest profit and cost ratio (3.28). The overall structure of tuna market is close to monopolistic market. The pricing system is carried out by bargaining agreement and the cooperation between marketing agencies is well established. Suggestions that can be given are need the local government support in terms of capital and fishermen must be able to take advantage of the fish market facilities that have been provided.